Translation of Hmong folklore terms in Hmong oral epic “creating heaven and earth” from the perspective of eco-translatology - Li, Xiong; Sim, Ng Boon; Mohd Zin, Zaid (Academy Publication, 2024)
The Hmong, a Chinese ethnic minority, possess a rich cultural heritage. Due to their unique history of exile and migration, the Hmong have scant documentation of their vanishing cultural heritage. The Hmong oral epic constitutes a vital component of documenting Hmong culture. Thus, this paper delves into the translation of the Hmong Oral Epic 'Creating Heaven and Earth', focusing on folklore terms as fundamental units for analyzing Hmong culture. Eco-Translatology has the great importance in protecting the languages of Chinese ethnic minorities and enhancing the dissemination of their literature (Li, 2017). Hence, this paper examines the translation of Hmong folklore terms in the Hmong Oral Epic 'Creating Heaven and Earth' from the perspective of Eco-Translatology. The study reveals 53 translations of Hmong folklore terms, encompassing material, social, and spiritual aspects, within the Hmong oral epic 'Creating Heaven and Earth'. For Hmong material folklore terms, translators predominantly employ the 'target contextualization' strategy, along with 'extending substitution' and 'vitalization' methods. For Hmong social folklore terms, translators favor the 'source contextualization' strategy, supplemented by 'adaptive addition' and 'vitalization' methods. For Hmong spiritual folklore terms, translators predominantly utilize the 'source contextualization' strategy, in addition to 'extending substitution' and 'naturalization' methods.